2018
DOI: 10.1002/adma.201704002
|View full text |Cite
|
Sign up to set email alerts
|

Organic–Inorganic Hybrid Halide Perovskites for Memories, Transistors, and Artificial Synapses

Abstract: Fascinating characteristics of halide perovskites (HPs), which cannot be seen in conventional semiconductors and metal oxides, have boosted the application of HPs in electronic devices beyond optoelectronics such as solar cells, photodetectors, and light-emitting diodes. Here, recent advances in HP-based memory and logic devices such as resistive-switching memories (i.e., resistive random access memory (RRAM) or memristors), transistors, and artificial synapses are reviewed, focusing on inherently exotic prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
168
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(169 citation statements)
references
References 142 publications
0
168
1
Order By: Relevance
“…Based on the Nernst equation, ions migration with low E A can easily occur when exposed to the thermal or operational condition and lead to the rapid degradation of PSCs. [49,50] According to the principle of resistance change, the conductive filaments are formed by ions migration in the films and the formation/broken of the conductive filaments controls resistance of memristor devices. [25] To investigate the suppression of ions migration by PbPyA 2 , we conduct the electric poling experiment with the structure of ITO/ Au/perovskite/Au (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the Nernst equation, ions migration with low E A can easily occur when exposed to the thermal or operational condition and lead to the rapid degradation of PSCs. [49,50] According to the principle of resistance change, the conductive filaments are formed by ions migration in the films and the formation/broken of the conductive filaments controls resistance of memristor devices. [25] To investigate the suppression of ions migration by PbPyA 2 , we conduct the electric poling experiment with the structure of ITO/ Au/perovskite/Au (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
“…The rapid increase of photovoltaic efficiency has been accompanied by a deeper understanding of the physical/chemical properties of OHPs . Recently, there has been interests in applying OHPs to other photonic and electronic devices, including light‐emitting diodes, X‐ray detectors, and energy conversion devices . It is expected that OHPs will become important active materials for next‐generation devices in the near future.…”
Section: Organic‐inorganic Halide Perovskitesmentioning
confidence: 99%
“…This remarkable achievement is attributed to the exceptional optoelectronic properties of OHPs such as high charge carrier mobility, tunable band gaps, high absorption coefficients, and long carrier diffusion lengths . These outstanding characteristics also extend their applications to light‐emitting diodes, photodetectors, and transistors, demonstrating the flexibility and potential of OHPs for optoelectronic device applications beyond photovoltaics. Recently, mixed ionic‐electronic conduction behavior was found in OHP‐based solar cells, suggesting the ion migration plays a nonnegligible role in devices with OHPs.…”
Section: Introductionmentioning
confidence: 99%
“…Some researches approved that the RS performances in devices based on all‐inorganic perovskites were more stable as compared with organic perovskites materials. So, promoting all‐inorganic perovskite‐based memory devices would further satisfy requirement in fashionable RS field …”
mentioning
confidence: 99%
“…On the basis of the aforementioned experimental analysis, the physical RS mechanism of the Au/Cs 4 PbBr 6 /PEDOT:PSS/ITO memory devices could be attributed to the conductive filamentary mode. Some literatures reported that in the perovskite‐based RS memory devices, ions can drift in the dielectric layer during the switching‐on process . On the basis of aforementioned analysis, the Br − ions related to the conductive filaments model were adopted to elucidate the physical mechanism.…”
mentioning
confidence: 99%